If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10=7x+6(x+7)
We move all terms to the left:
-10-(7x+6(x+7))=0
We calculate terms in parentheses: -(7x+6(x+7)), so:We get rid of parentheses
7x+6(x+7)
We multiply parentheses
7x+6x+42
We add all the numbers together, and all the variables
13x+42
Back to the equation:
-(13x+42)
-13x-42-10=0
We add all the numbers together, and all the variables
-13x-52=0
We move all terms containing x to the left, all other terms to the right
-13x=52
x=52/-13
x=-4
| 7x-3+2x=7x-3 | | 3(x-2)=-4(-x+4) | | -7p+-2p=-18 | | -10=1.5c=2 | | -2+y/10=6 | | -7a+6(8a+3)=182 | | (3x-5)(x+1)=180 | | -12=-3-4m+7m | | 2(5+7p)-3=7(4p-7) | | x+6+6x-58=180 | | 1.3-x+2.1=5.7 | | b-5.73=3.27 | | 2m-3)m+1)=4(m+3) | | 12(x−5)=11(x+5) | | 148=4(1-6n) | | x+5=(x–2)–(2x–7) | | 106-11x(11x)=0 | | 10(-5x+6)-9=1+5(-10x+10) | | 4-3x+8x-4-4x=12 | | 4(3x-11)=12x | | 4x+23+10x-1=24 | | 2x-3(x+2)=5 | | 3x(4x-40)=360 | | 3x-3-3=9 | | 36p=61 | | 49-3m=4m+14* | | 99.9x=24.9 | | 4-3x=8x-4-4x=12 | | 5x+x+4+3x+4=41 | | k+5/3=7/2 | | 5-(x-8)=2(x+10) | | -4=5x-17-22x |